PEMANFAATAN KAYU AKASIA MANGIUM (Acacia mangium Willd) UNTUK MEBEL - Djoko Purwanto (Kementerian Perindustrian, 2012)
Timber Acacia mangium (Acacia mangium, Willd) for Furniture. The study aims to determine the mechanical and physical properties and the decorative value (color and fiber) wood of acacia mangium with using finishing materials. This type of finishing material used is ultran lasur natural dof ,ultran lasur classic teak, aqua politur clear dof, aqua politur akasia dan aqua politur cherry. After finishing the wood is stored for 3 months. Test parameters were observed, namely, physical and mechanical properties of wood, adhesion of finishing materials, color and appearance of the fiber, and timber dimensions expansion. The results showed that the mechanical physical properties of acacia wood qualified SNI. 01-0608-89 about the physical and mechanical properties of wood for furniture, air dry the moisture content from 13.78 to 14.89%, flexural strength from 509.25 to 680.50 kg/cm2, and compressive strength parallel to fiber 342.1 - 412.9 kg/cm2. Finishing the treatment process using five types of finishing materials can increase the decorative value (color and fiber) wood. Before finishing the process of acacia mangium wood has the appearance of colors and fibers and less attractive (scale scores 2-3), after finishing acacia wood fibers have the appearance of colors and interesting and very interesting (scale 4-5).Keywords: mangium wood, mechanical properties, decorative value, finishing, furniture.